2017
DOI: 10.3390/cells7010002
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell-Derived Red Blood Cells and Platelet Concentrates: From Bench to Bedside

Abstract: Red blood cells and platelets are anucleate blood components indispensable for oxygen delivery and hemostasis, respectively. Derivation of these blood elements from induced pluripotent stem (iPS) cells has the potential to develop blood donor-independent and genetic manipulation-prone products to complement or replace current transfusion banking, also minimizing the risk of alloimmunization. While the production of erythrocytes from iPS cells has challenges to overcome, such as differentiation into adult-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…High enucleation rates have been described for in vitro culture systems that initiate from cord blood, fetal or adult CD34+ hematopoietic stem and progenitor cells ( Leberbauer et al, 2005 ; van den Akker et al, 2010a ; Giarratana et al, 2011 ). In contrast, enucleation is generally poor in immortalized cell lines and erythroid cells derived from induced pluripotent stem cells ( Lapillonne et al, 2010 ; Kurita et al, 2013 ; Trakarnsanga et al, 2017 ) [reviewed by ( Focosi and Amabile, 2017 )]. Resolving the fine details of the enucleation process and events leading up to enucleation may facilitate and improve the production of erythrocytes from these immortal sources.…”
Section: Enucleationmentioning
confidence: 99%
“…High enucleation rates have been described for in vitro culture systems that initiate from cord blood, fetal or adult CD34+ hematopoietic stem and progenitor cells ( Leberbauer et al, 2005 ; van den Akker et al, 2010a ; Giarratana et al, 2011 ). In contrast, enucleation is generally poor in immortalized cell lines and erythroid cells derived from induced pluripotent stem cells ( Lapillonne et al, 2010 ; Kurita et al, 2013 ; Trakarnsanga et al, 2017 ) [reviewed by ( Focosi and Amabile, 2017 )]. Resolving the fine details of the enucleation process and events leading up to enucleation may facilitate and improve the production of erythrocytes from these immortal sources.…”
Section: Enucleationmentioning
confidence: 99%
“…The establishment of imMKCLs represents an important advance toward generating large numbers of iPSC-derived platelets ex vivo, but the low PLP yield and requirement of mouse somatic feeder cells are major hurdles that must be overcome before clinical realization. 33 In the current study, we present experimental and practical details of a b1-tubulin-Venus reporter line that promises to accelerate our search for optimal conditions for imMKCL Compounds/M By screening .5000 compounds, a series of candidates were identified from distinct categories that were not reported to promote MK maturation and PLP production (Figure 2). Wnt-C59 and TCS 359 are known inhibitors of WNT signaling and FLT3, respectively; however, other compounds exhibiting similar inhibitor effects on WNT and FLT3 signaling did not show similar effects in the reporter cell line ( Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…A challenge for the PSC or iPSC differentiation, as also mentioned above in the iPSC-derived MNs, is that the PSC-derived cells tend to be immature. This is indeed the major limitation for translating iPSC-derived red blood cells into the clinic [25]. In 2008, Lu et al reported differentiation of human ES cells into functional oxygencarrying erythrocytes on a large scale with up to 60% enucleation rate [26].…”
Section: Ipsc-based Therapiesmentioning
confidence: 99%